Negative emotional reactivity as a marker of vulnerability in the development of borderline personality disorder symptoms. (30th April 2015) - Stepp, Stephanie D.; Scott, Lori N.; Jones, Neil P.; Whalen, Diana J.; Hipwell, Alison E.
Abstract: Negative emotionality is a distinguishing feature of borderline personality disorder (BPD). However, this person-level characteristic has not been examined as a marker of vulnerability in the development of this disorder. The current study utilized a multimethod approach to examine the interplay between negative emotional reactivity and cumulative exposure to family adversity on the development of BPD symptoms across 3 years (ages 16–18) in a diverse, at-risk sample of adolescent girls ( N = 113). A latent variable of negative emotional reactivity was created from multiple assessments at age 16: self-report, emotion ratings to stressors from ecological assessments across 1 week, and observer-rated negative affectivity during a mother–daughter conflict discussion task. Exposure to family adversity was measured cumulatively between ages 5 and 16 from annual assessments of family poverty, single parent household, and difficult life circumstances. The results from latent growth curve models demonstrated a significant interaction between negative emotional reactivity and family adversity, such that exposure to adversity strengthened the association between negative emotional reactivity and BPD symptoms. In addition, family adversity predicted increasing BPD symptoms during late adolescence. These findings highlight negative emotional reactivity as a marker of vulnerability that ultimately increases risk for the development of BPD symptoms.